Nový pohled na prenos a cirkulaci viru klíst'ové encefalitidy v prírodĕ - Danielová, V (Epidemiologie, mikrobiologie, imunologie, 1994)
The author summarizes briefly the results of experiments which provide evidence of non-viraemic transmission of the virus from infected to non-infected ticks during co-feeding on a non-viraemic host. This mode of transmission originally found in the Thogoto virus and its vector, the tick Rhipicephalus appendiculatus, was proved also in the virus of tick-borne encephalitis and its vector Ixodes ricinus. Based on this fact some conclusions are drawn revising the accepted view regarding the life cycle of tick-borne encephalitis virus in nature and in particular the relationship: vector-host-virus.
Keywords: klíšťová encefalitida; arachnida jako vektory; klíšťata; Moles; krtci; Arachnid Vectors; Animals; Ticks; viry klíšťové encefalitidy; Guinea Pigs; zvířata; Encephalitis, Tick-Borne; Encephalitis Viruses, Tick-Borne; morčata